Experimental study on spatial emission spectrum characteristics in a dielectric barrier discharge component for ar atmospheric pressure plasma jet formation - Goto, Tomoha; Midi, Nur Shahida; Ohyama, Ryu-ichiro (IEEE, 2015)
Atmospheric pressure plasma is type of plasma that doesn’t need low-pressure apparatus system. Compared to other procedure in generating atmospheric pressure plasma jet, the application of the dielectric barrier discharge (DBD) is comparatively simple. However, the details regarding the electric discharge properties and active species’ forming reaction is still unclear. It is also important to understand the plasma generation region, which is the key component of DBD for the application in future works. Therefore in this work, the generation region of Ar plasma caused by dielectric barrier discharge was investigated. The atmospheric pressure plasma generating device used in this experiment was constructed by covering a part of a copper pipe, which act as an electric discharge electrode with a silica glass pipe. As a grounding electrode, the exterior part of the silica glass pipe was wrapped with a copper foil. This plasma was examined using emission spectroscopy method from the side of the silica glass pipe. The copper foil was provided with a slit for measuring the emission spectroscopy in the grounding electrode area. The measurement was ranged from the edge of copper pipe until the end of plasma emission. From the results, spatial emission spectrum of excited Ar had shown different emission intensity according to the point location. This paper discusses about the spatial emission characteristics by focusing on the dielectric barrier.